Stock Investment Behavior of the Millennial Generation: The Moderating Role of Financial Literacy - Andreas Gelbert Hariputra Alva; Maria Rio Rita (BASKARA : Journal of Business and Entrepreneurship, 2022)
The purpose of this research is to analyze the investment behavior of the millennial generation in Indonesia. The independent variables in this research are gender, income, and social environment. The dependent variable is investment behavior, while financial literacy is the moderating variable. The sample of this research was determined based on the purposive sampling method. There were 144 respondents selected from the millennial generation who were in the age range of 21-41 years old and had invested in stocks. The data collection was carried out online by distributing questionnaires through Google Forms in a WhatsApp group and a stock investment community Telegram group. The analysis technique used was a Moderated Regression Analysis (MRA). This research found that income and gender have no effect on the millennial generation’s stock investment behavior. Financial literacy is not confirmed to moderate the effect of income on investment behavior and the effect of gender on investment behavior. However, the social environment has a significant positive effect on investment behavior, and there is evidence that financial literacy moderates the influence of the social environment on the stock investment behavior of the millennial generation.